2018
DOI: 10.1002/dmrr.3064
|View full text |Cite
|
Sign up to set email alerts
|

Distinct neutrophil counts and functions in newly diagnosed type 1 diabetes, latent autoimmune diabetes in adults, and type 2 diabetes

Abstract: Neutrophil numbers and migration abilities displayed distinct levels in different types of diabetes. In T1D, CD62L seems to play an important role in the migration of neutrophils and β-cell autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 36 publications
4
61
3
2
Order By: Relevance
“…Neutrophils are the first-line immune cells involved in inflammation, and circulating neutrophil counts are moderately increased in type 2 diabetes [3,7]. However, the role of neutrophils in the pathogenesis of type 2 diabetes is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophils are the first-line immune cells involved in inflammation, and circulating neutrophil counts are moderately increased in type 2 diabetes [3,7]. However, the role of neutrophils in the pathogenesis of type 2 diabetes is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are the most abundant type of white blood cell and are reported as active players in inflammation of obesity-related insulin resistance [2]. Additionally, neutrophil count, a marker of subclinical inflammation, has been shown to significantly increase in type 2 diabetes compared with healthy subjects [3][4][5]. Neutrophil-lymphocyte ratio significantly increases in prediabetes and diabetes and may be a predictive marker for prediabetes and diabetes mellitus [6].…”
Section: Introductionmentioning
confidence: 99%
“…Older studies have shown that in T1DM patients, there is an increase in neutrophil counts compared to healthy individuals [38,39]. Recent researches described a decrease in circulating neutrophil numbers in T1DM patients in comparison with nondiabetics [40,41]. Impairment in neutrophil yield and maturation in bone marrow, increase in peripheral neutrophil consumption, and/or tissue sequestration could explain this reduction in blood neutrophil counts observed in T1DM [42].…”
Section: Impaired Neutrophil Migration In Diabetesmentioning
confidence: 99%
“…This divergence between studies can be attributed to differences between ethnic groups and the discovery of the existence of various stages of DM [43]. While in T1DM, the data about circulating neutrophil counts are still controversial, most of the studies Neutrophil Function Impairment Is a Host Susceptibility Factor to Bacterial Infection in Diabetes DOI: http://dx.doi.org/10.5772/intechopen.86600 described that in T2DM patients, there is an increase in the number of neutrophils in circulation in comparison to healthy individuals [40,44]. This neutrophilia was related to elevation in the circulation levels of inflammatory cytokines, including TNF-α, IL-1β, and IL-6, and CRP, a known marker of inflammation [45].…”
Section: Impaired Neutrophil Migration In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation